Understanding the Hadith of Lubs al-Syuhrah and the Historical Facts of Robes and Turbans as the Identity of Nusantara Ulama - Wilaela Wilaela; Nur Aisyah Zulkifli; Masduki Masduki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the evolution of clerical attire, specifically the so-called Arab or hajj attire, comprising robes and turbans, and its role in shaping the identity of Nusantara clerics over centuries. In the context of the Hadith of the Prophet Muhammad, the question of the relevance of Arab attire to the Nusantara is a subject of divergent scholarly opinion. Some clerics consider it to be irrelevant, whilst others regard it as sunnah fi'liyah, analysing it from an ethical and aesthetic perspective. The present study employs qualitative methods, with a focus on historical approaches. To this end, it utilises a range of sources, including autobiographies and biographies, visual materials, such as images of clerics, and a series of interviews conducted with 19 individuals who are both historical witnesses and relatives of the aforementioned clerics. It is evident that in the 19th century, the adherents of Islam in the region of Riau were distinguished by their distinctive attire, which included the wearing of robes and turbans. The scholars' attire represented their elevated economic, social, and political status, in addition to their substantial religious authority. The robe and turban also became symbols of the scholars' anti-colonial struggle. The historical and cultural factors that influenced this acceptance included the Hajj pilgrimage, colonial government regulations pertaining to Hajj attire, the harmonisation of Arab attire with Malay culture, and the emergence of Sufi movements. Nevertheless, since the 20th century, the attire of Islamic scholars has experienced substantial modification, primarily due to the integration of Western educational frameworks and the rise of the contemporary Indonesian elite. The attire of clerics in Riau comprises trousers, Western-style suits, ties, and hats, in addition to skullcaps or peci, which collectively serve to establish a uniform appearance that mirrors that of other Indonesian intellectuals who have undergone modern educational pursuits. Moreover, religious attire in the form of robes and turbans began to be adopted as a collective identifier, rather than exclusively as a religious or clerical vestment, by certain Muslim communities